In‐depth cardiovascular and pulmonary assessments in children with multisystem inflammatory syndrome after SARS‐CoV‐2 infection: A case series study. Issue 5 (11th March 2022) - Astley, Camilla; Badue Pereira, Maria Fernanda; Lima, Marcos Santos; Buchpiguel, Carlos Alberto; Carneiro, Camila G.; Sapienza, Marcelo Tatit; Leal, Gabriela Nunes; do Prado, Danilo Marcelo Leite; Peçanha, Tiago; Sieczkowska, Sofia Mendes; Matsuo, Olivia Mari; Lindoso, Livia; et al.
Abstract: We assessed PET‐CT myocardial blood flow (MBF) using N‐13 ammonia, brachial flow‐mediated dilation, and cardiopulmonary exercise test in five post‐discarged MIS‐C survivors. None of the patients (median age: 9, range: 7‐18 years; 3 females; 2 males) had preexisting pediatric chronic conditions. At the follow‐up visit, two patients exhibited severe perfusion defect developed in the left ventricular cavity, suggesting extensive myocardial ischemia (MBF <2.0) and one patient showed persistent mild pericardial effusion. Others two patients demonstrated endothelial dysfunction. Nevertheless, all patients had lower predicted values in the V O2peak, V O2VAT, OUES, and O2 Pulse (range: 35.2%–64.5%; 15.6%–38.2%; 1.0–1.3 L/min; 4–7 ml/beat), respectively. Our d suggested that previously health MIS‐C patients had impaired MBF, endothelial dysfunction and lower cardiopulmonary capacity at follow‐up analysis. Multidisciplinary further investigations should be conducted to reinforce these findings. Abstract : Previously health multisystem inflammatory syndrome in children (MIS‐C) patients showed impaired myocardial flow reserve, endothelial dysfunction, and lower cardiopulmonary capacity after 1.9 months of infection. Our findings reveal novel pathophysiological findings in MIS‐C patients, which advances the knowledge on this newly described condition and may help tailor better treatments for these patients.